Cannabis-induced obsessive-compulsive disorder: Is it a paradox? - Rashmi Shukla; Nalin Shukla (Indian Journal of Psychiatry)
The case of a 22-year-old man with cannabis-induced obsessive-compulsive disorder (OCD) is described in this case report. There is ample literature available regarding cannabis-induced psychotic and mood symptoms but there is dearth of literature about cannabis association with OCD. The importance of recognising cannabis-induced OCD is emphasized, given that in literature, it can be used in ameliorating OCD in a few studies. Nevertheless, further research is needed to explore the neurobiological underpinning of both cannabis abuse and OCD to find out the link and complex interplay between addictive, impulsive and compulsive behaviours before using it as a treatment option.